Optimal coordination of protective relays - Nair, D. S.; Reshma, S. (2013 International Conference on Power, Energy and Control (ICPEC), 2013)
Protective relays are commonly used as an economical means for protecting power systems. The selection of appropriate settings of these relays under various system conditions plays an important role in timely removal of the faulty section of power system. Distance and overcurrent relays are mainly used for transmission and sub transmission protection system. To consider comprehensive coordination, a distance relay with a distance one, an overcurrent relay with an overcurrent one and finally a distance relay with an overcurrent one when one of them is considered to be the main relay and the other is the backup, must be coordinated. In many sub-transmission and transmission power systems directional overcurrent relays are used as secondary protection, the main protection schemes use distance relays. In the project a new optimal method for overcurrent and distance relay coordination based on Genetic algorithm has been developed. In the optimal methods, the operating times of the relays are minimized in the frame of the objective function, subject to coordination constraints, relay characteristic curves and the limits of the relay settings. Various relay characteristics is considered for each overcurrent relay and best of them is selected by genetic algorithm to make optimal coordination.